Evaluation Effectiveness of Implementation Training on Making ICT-Based Learning Media for Teachers - Dian Anatalia Sulistianingtyas; Andi Mariono; Bachtiar Syaiful Bachri (IKIP Mataram, 2022)
This research aims to determine the effectiveness implementation of training in making ICT-based learning media for teachers. This evaluation research uses the CIPP evaluation model from Stuffelbeam with quantitative and qualitative approaches. The subjects of this study were participants, instructors and training providers, with the object of research being documentation of the implementation of ICT-based media creation training, the instructor's performance, and the work and impact reports of the training participants. Based on the results of the research evaluation of the effectiveness of the implementation of training in making ICT-based learning media for teachers at LPMP West Sulawesi, it can be results (1) Context Aspect is the suitability of the objectives of the implementation of the training program for making ICT-based learning media with the Vision and Mission of the LPMP West Sulawesi. The training service was considered very satisfactory at 93% and declared effective at 7%. (3) In the process aspect, the trainees assessed that the performance of the training instructor was very effective, 95% of the respondents gave an assessment of being very effective and the remaining 5% gave an effective assessment of the instructor's performance. (4) Product Aspect, the percentage of teachers who can fulfill the assignment requirements is 95% for video work or about 40 teachers from a total of 42 participants, while for impacting there are 39 teachers who submit impact reports or around 93%. The implementation of training on making ICT-based learning media for teachers at the West Sulawesi LPMP is running effectively.